ICT-Based Learning During Covid-19 Outbreak: Advantages, Opportunities and Challenges - Abdullah M. Al-Ansi; Askar Garad; Ahmed Al-Ansi (Gagasan Pendidikan Indonesia, 2021)
ICT-based learning is kind of learning that use Information and Communication Technology (ICT) to foster, optimize, enhance and support gaining knowledge. Covid-19 has caused the full transformation to ICT-based learning. This study aimed to investigate the advantages, opportunities and challenges of ICT-BL during the pandemic. Systematic analysis of the qualitative results indicated that possibility of Online learning, saving time and money, communication and motivation tool, usage of social media, sharing and processing the knowledge and improving the quality of education were the highest ranked advantages of the ICT-based learning and remote learning, extra time, adoption of new skills and more technologies and MOOCs in addition to family gathering were the most opportunities while internet accessibility, electricity problems, maintenance of infrastructure, high cost of ICT device and lack of expertise, ability to manage classrooms and plagiarism were the high ranked challenges for both students and lecturers to continue online learning. Developing countries need to develop new strategies and techniques to promote ICT-based learning based on innovation, socio-cultural and socio-economic aspects not only financial support.